Intention to use and acceptability of home-based sexual health care among men who have sex with men who previously attended clinic-based sexual health care - Goense, Cornelia J. D.; Evers, Ymke J.; Hoebe, Christian J. P. A.; Crutzen, Rik; Dukers-Muijrers, Nicole H. T. M. (Frontiers in Reproductive Health, 2022)
The COVID-19 pandemic has temporarily disrupted access to clinic-based sexual health care for men who have sex with men (MSM) in the Netherlands. The importance of home-based sexual health care has been underpinned as an extension of clinic-based care. This paper aims to assess intention to use, and acceptability of home-based sexual health care among MSM who previously attended clinic-based sexual health care. In November 2020, 424 MSM who had attended an STD clinic pre-pandemic were invited to participate in an online survey; 154 MSM completed the survey (response 36%). Intention to use self-sampling STD/HIV tests was assessed (median; scale 0-100) and compared across sociodemographic and sexual behavior characteristics by Kruskal-Wallis H tests. Descriptive analyses provided insights in acceptability of home-based sexual health care. Of participants (median age 47), 60.4% (93/154) tested for STD/HIV in the past six months, most of them attended a clinic. The median score on intention to use self-sampling tests was 86.5 (SD=33.4) and did not differ by sociodemographic or sexual behavioral characteristics (all p-values > 0.1). Participants were positive towards online sexual health counseling (median attitude= 75.0, SD=29.6) and their main preferred topics were PrEP use and STD/HIV testing. MSM who attended clinic-based care expressed intention to use self-sampling tests and a positive attitude towards online sexual health counseling. Home-based sexual health care elements are not currently integrated within Dutch clinic-based sexual health care and should be considered an addition for continued provision of care and extended reach of MSM.